Obligatory use of the videotape recording on the competitions of all levels as a major factor of increase of objectivity of judging is in the amateur boxing - Вострокнутов, Л. Д.; Булгаков, Д. О.; Єрьоменко, В. В. (Slobozhanskyi Herald of Science and Sport, 2011)
Expediency of the use of the videotape recording of duel is grounded on boxing on the competitions of different level., that will assist maintenance of health of sportsmen, to more effective preparation of the Ukrainian boxers to appearance on competitions, will reduce the amount of judge errors, will promote responsibility of judge corps for the actions and objectivity made decision. Fights and results of competitions are analysed 2010 - 2011 years, the selective questionnaire of participants is conducted on issue of the preconceived and biased judging in boxing.